Bank Insolvencies, Regulatory Forbearance and Ambiguity - Dmitri V. Vinogradov (University of Heidelberg, Department of Economics, 2006)
Banking regulators often practice forbearance and ambiguity in insolvency resolutions. The paper examines the effects of regulatory forbearance and ambiguity in a context of allocational efficiency. Bailouts, liquidations and their stochastic policy mix lead to suboptimal allocations if banks do not internalize insolvency costs. The policy of forbearance may make banks internalizing such costs and improves the efficiency of intermediation.
Keywords: D50; E44; G21; G28; 330; Banks; insolvency resolution; forbearance; constructive ambiguity; Bankenregulierung; Bankinsolvenz; Wirkungsanalyse; Allokationseffizienz; Theorie